2003
DOI: 10.1073/pnas.0831246100
|View full text |Cite
|
Sign up to set email alerts
|

Non-self recognition, transcriptional reprogramming, and secondary metabolite accumulation during plant/pathogen interactions

Abstract: Disease resistance of plants involves two distinct forms of chemical communication with the pathogen: recognition and defense. Both are essential components of a highly complex, multifaceted defense response, which begins with non-self recognition through the perception of pathogen-derived signal molecules and results in the production, inter alia, of antibiotically active compounds (phytoalexins) and cell wall-reinforcing material around the infection site. To elucidate the molecular details and the genomic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
113
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(124 citation statements)
references
References 31 publications
4
113
0
6
Order By: Relevance
“…Nevertheless, our present data on A. thaliana, as well as those (Fig. 5) extending earlier studies on cultured P. crispum cells (Kauss et al, 1993;Franke et al, 1998), are in full accord with, and further confirm, the general conclusion (Hahlbrock et al, 2003) that the three analogous series of 4-hydroxy-, 4-hydroxy-3-methoxy-, and 4-hydroxy-3,5-dimethoxybenzaldehyde, -benzoate and -cinnamate together constitute a characteristic set of universally occurring, aromatic cell wall-bound compounds in higher plants.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, our present data on A. thaliana, as well as those (Fig. 5) extending earlier studies on cultured P. crispum cells (Kauss et al, 1993;Franke et al, 1998), are in full accord with, and further confirm, the general conclusion (Hahlbrock et al, 2003) that the three analogous series of 4-hydroxy-, 4-hydroxy-3-methoxy-, and 4-hydroxy-3,5-dimethoxybenzaldehyde, -benzoate and -cinnamate together constitute a characteristic set of universally occurring, aromatic cell wall-bound compounds in higher plants.…”
Section: Discussionsupporting
confidence: 82%
“…Large changes in secondary metabolism, including the accumulation of phytoalexins and aromatic cell wallbound compounds, are among the earliest detectable results of the extensive transcriptional reprogramming that occurs in challenged plant cells during plant/ pathogen interactions (Somssich and Hahlbrock, 1998;Dixon, 2001;Hahlbrock et al, 2003). Using soluble extracts from Arabidopsis thaliana leaves, we have previously shown that, in addition to the characteristic phytoalexin of this species, camalexin, several other indolic metabolites were strongly and rapidly induced upon infection.…”
Section: Introductionmentioning
confidence: 99%
“…The less frequently occurring box A (28) is not present in any one of the four At4CL gene promoters without at least one (At4CL3) or two (At4CL4) mismatches. An absolute singularity among all known 4CL genes is the occurrence of three perfect TATA-proximal W-box sequences (25) in the At4CL4 gene promoter, two of which have recently been shown to fulfil the operational W-box criterion of WRKY transcription factor binding (14).…”
Section: Comparative Analysis and Definition Of The Complete At4cl Genementioning
confidence: 99%
“…This latter discovery, in the context of our long-term interest in understanding the functional diversity of phenylpropanoid metabolism in conjunction with its genetic background in A. thaliana (14), prompted us to further characterize this rare sinapate-activating At4CL and define its position within the At4CL gene family. Here, we verify its identity as a previously undetected fourth isoenzyme (At4CL4) in A. thaliana, compare its structural and putative functional characteristics with those of the other three family members, propose a sequence for the stepwise evolution of the four At4CLs as a basis for the diversification of phenylpropanoid metabolism, and discuss the results in relation to the substructure of the overall plant 4CL superfamily.…”
mentioning
confidence: 99%
“…[1][2][3][4] Experiments designed to study such intricate networks often have a complex factorial structure, obtained by assessing plant responses in different conditions/treatments, tissue types or genetic contexts. Among the major problems associated with the statistical analysis of multifactorial experimental designs are those of gene prioritization and of large numbers of false positives.…”
mentioning
confidence: 99%